Challenges constraining availability and affordability of insulin in Bengaluru region (Karnataka, India): evidence from a mixed-methods study - Gautam Satheesh; M. K. Unnikrishnan; Abhishek Sharma (Taylor & Francis Group, 2019)
Introduction Considering limited global access to affordable insulin, we evaluated insulin access in public and private health sectors in Bengaluru, India. Methods Employing modified WHO/HAI methodology, we used mixed-methods analysis to study insulin access and factors influencing insulin supply and demand in Bengaluru in December 2017. We assessed insulin availability, price and affordability in a representative sample of 5 public-sector hospitals, 5 private-sector hospitals and 30 retail pharmacies. We obtained insulin price data from websites of government Jan Aushadhi scheme (JAS) and four online private-sector retail pharmacies. We interviewed wholesalers in April 2018 to understand insulin market dynamics. Results Mean availability of insulins on India's 2015 Essential Medicine List was 66.7% in the public sector, lower than private-sector retail (76.1%) and hospital pharmacies (93.3%). Among private retailers, mean availability was higher among chain (96.7%) than independent pharmacies (68.3%). Non-Indian companies supplied 67.3% products in both sectors. 79.1% products were manufactured in India, of which 60% were marketed by non-Indian companies. In private retail pharmacies, median consumer prices of human insulin cartridges and pens were 2.5 and 3.6 times, respectively, that of human insulin vials. Analogues depending on delivery device were twice as expensive as human insulin. Human insulin vials were 18.3% less expensive in JAS pharmacies than private retail pharmacies. The lowest paid unskilled worker would pay 1.4 to 9.3 days' wages for a month's supply, depending on insulin type and health sector. Wholesaler interviews suggest that challenges constraining patient insulin access include limited market competition, physicians' preference for non-Indian insulins, and the ongoing transition from human to analogue insulin. Rising popularity of online and chain pharmacies may influence insulin access. Conclusion Insulin availability in Bengaluru's public sector falls short of WHO's 80% target. Insulin remains unaffordable in both private and public sectors. To improve insulin availability and affordability, government should streamline insulin procurement and supply chains at different levels, mandate biosimilar prescribing, educate physicians to pursue evidence-based prescribing, and empower pharmacists with brand substitution. Patients must be encouraged to shop around for lower prices from subsidized schemes like JAS. While non-Indian companies dominate Bengaluru's insulin market, rising market competition from Indian companies may improve access.